The Beneficial Effect of IL-12 and IL-18 Transduced Dendritic Cells Stimulated with Tumor Antigens on Generation of an Antitumor Response in a Mouse Colon Carcinoma Model - Jagoda Mierzejewska; Katarzyna Węgierek-Ciura; Joanna Rossowska; Agnieszka Szczygieł; Natalia Anger-Góra; Bożena Szermer-Olearnik; Magdalena Geneja; Elżbieta Pajtasz-Piasecka (Journal of Immunology Research)
The main purpose of our study was to determine the effect of dendritic cell (DC) transduction with lentiviral vectors carrying sequences of il18 and/or il12 genes on the level of antitumor activity in vitro and in vivo. We examined the ability of DCs to migrate to the tumor-draining lymph nodes and infiltrate tumor tissue and to activate the local and systemic antitumor response. On the 15th day, DCs genetically modified for production of IL-12 and/or IL-18 were administered peritumorally to C57BL/6 female mice with established MC38 tumors. Lymphoid organs and tumor tissue were collected from mice on the 3rd, 5th, and 7th days after a single administration of DCs for further analysis. Administration of DCs transduced for production of IL-12 alone and in combination with IL-18 increased the inflow and activity of CD4+ and CD8+ T lymphocytes in the tumor microenvironment and tumor-draining lymph nodes. We also found that even a single administration of such modified DCs could trigger a systemic antitumor response as well as inhibit tumor growth. Application of the developed DC-based vaccines may exert a favorable impact on stimulation of an antitumor immune response, especially if these DC vaccines are administered repeatedly.